Anticipated Emotions About Unintended Pregnancy in Relationship Context: Are Latinas Really Happier?. Issue 2 (28th July 2016) - Aiken, Abigail R. A.; Trussell, James
Abstract: This study examined differences in women's anticipated emotional orientations toward unintended pregnancy by relationship status and race and ethnicity. Data from a prospective survey of 437 women aged 18 to 44 years who intended no more children for at least 2 years were analyzed along with 27 in‐depth interviews among a diverse subsample. Cohabiting women and women in romantic relationships not living together were less likely to profess happiness (odds ratio = 0.42, p < .05, odds ratio = 0.25, p < .01, respectively), even when partners' intentions and feelings were controlled. The most prominent factor underlying negative feelings was partners' anticipated lack of engagement with the emotional, physical, and financial toll of unintended childbearing. Contrary to conventional wisdom regarding the "Hispanic paradox, " foreign‐born and U.S.‐born Latinas were no more likely to profess happiness than non‐Hispanic Whites or Blacks. Moreover, foreign‐born Latinas whose survey responses indicated happiness often revealed highly negative feelings at in‐depth interview, citing pressure to conform to sociocultural norms surrounding motherhood and abortion.